Analisa Pengaruh Penggunaan Internet Terhadap Minat Belajar Siswa SMP Menggunakan Metode Naïve Bayes - Puji Lestari, Dyta; Zakaria, Hadi (CV. Shofanah Media Berkah, 2024)
SMP S Islam Cikuda is one of the educational units with a junior high school level, which is located on Jalan Raya Cikuda No 1, Parungpanjang District, Bogor Regency 16360. The internet has become an integral part of daily life, including in the context of education. The use of the internet is becoming more widespread among students. Many students access the internet to seek information, study, and communicate. A problem that often causes concern in junior high schools is that students use the internet as a place of entertainment and play games. Schools face obstacles in monitoring how the use of the internet affects students' interest in learning, especially related to the subject matter taught by teachers. This is important to understand the extent of the influence of internet use on students' interest in learning. To overcome this problem, the researcher used the Naïve Bayes method to analyze the correlation between internet use and students' interest in learning. In this study, the author uses the PHP programming language and data storage using a Mysql database. The researcher analyzed the use of the internet on students' learning interests, the analysis stage of the Bayes naives calculation in this study was carried out by a classification method that had been obtained from the training data/vocabulary of the observation results. With this research, it is hoped that schools can find out the influence of internet use on students' learning interests, which can be used by teachers to make wiser decisions about learning materials to be given in class, and can help teachers to understand what is more interesting to students, and change learning strategies according to students' learning interests.